DETERMINAN KEPUASAN KERJA PEGAWAI MELALUI EFEKTIFITAS KERJA: PERAN MOTIVASI KERJA, PELATIHAN DAN PENGEMBANGAN KARIR PADA BKPSDM PROVINSI PAPUA BARAT DAYA - Yunus Yunus; Vebby Anwar; Pahmi Pahmi (POLITEKNIK LP3I JAKARTA, 2026)
This study examines the determinants of job satisfaction through work effectiveness by positioning work motivation and training and career development as antecedents at BKPSDM Southwest Papua Province. A quantitative explanatory research design was applied. Data were collected through questionnaires distributed to 32 employees and analyzed using SPSS 26 for descriptive statistics and SmartPLS 4 for SEM-PLS testing. Findings reveal that work motivation has a positive but insignificant effect on work effectiveness and job satisfaction. Training and career development have positive and significant effects on work effectiveness and job satisfaction. Work effectiveness also has a positive and significant effect on job satisfaction. The mediation test shows that work effectiveness does not mediate the relationship between work motivation and job satisfaction, but significantly mediates the relationship between training and career development and job satisfaction. This study is limited to one public agency with a small population, so generalization should be cautious. Its originality lies in testing a civil servant job satisfaction model in a newly established province by integrating career development, work effectiveness, and BKPSDM’s institutional context.